التحليل الاقتصادي للبصمة البيئية كاداة لتحقيق التنمية المستديمة لعينة من الدول النامية لسنة (2020) - نجیب, شیماء محمد (Sulaimani Journal for Humanities, 2022)
Environmental economists focus on identifying tools that improve environmental conditions to achieve comprehensive sustainability, and reduce the depletion of limited natural resources, and those tools used in measurement (the ecological footprint), which is a tool that determines the amount of human demand for limited natural resources, not non-renewable, and nature's ability to Meeting these demands and their ability to renew to meet the needs of the next generation, and from this point of view, the ecological footprint is an indicator that measures the renewal of the limited natural resources consumed by humans, through its performance as a tool representing the area produced from the land for natural capital, as it represents the productive and environmental capacity of the land to renew natural resources and capacity waste absorption and recycling.Each country has its own environmental footprint, according to its needs, and according to the area of its productive land and its exploitation of natural resources. And the ecological footprint in developing countries is less efficient, that is, they consume limited natural resources, such as arable lands, more than the environment's ability to renew those resources, which leads to an increase in the environmental deficit. The research aims to prepare a proposed model for measuring sustainable development with the ecological footprint index. The research also assumes that the ecological footprint is used as a solution and as a viable tool in measuring the sustainable development of the biological and environmental field compared to its ability to renew itself. The research reached several conclusions, including the ability of the environmental footprint to measure sustainable development by calculating the environmental deficit and the depletion of limited natural resources. The research concluded from the practical side that the largest environmental footprint in the sample countries was represented in (Iran, followed by Turkey, Syria, Iraq and Saudi Arabia), The largest environmental deficit was in (Turkey, then Iran, followed by Syria, Iraq and Saudi Arabia), and the research suggested several proposals, among which it is necessary to transform the policies of expansion in economic growth from an excessive policy in the use of limited natural resources to a growth concerned with preserving limited natural resources, taking into account not to harm share for future generations.
Keywords: ecological footprint; sustainable development; biological capacity; environmental deficit; limited natural resources